TRANSFORMATION OF HIGHER EDUCATION IN MODERN CONDITIONS - I.V. Boyko; O.P. Bukhanchenko; V.M. Havryliev; V.V. Bondarenko (Український стоматологічний альманах)
The replacing of world civilization and Ukrainian society in particular played a significant role in the evolution of medical education in Ukraine. The system of higher education simultaneously affects the development of the future generation of doctors and is a remarkable social institution. That is why, the role of the system of higher medical education in difficult periods of the state’s development and proposed ways to innovate and optimize the scientific potential of students of higher medical education was analyzed.